2019
DOI: 10.1016/j.cemconres.2019.105865
|View full text |Cite
|
Sign up to set email alerts
|

Stability criterion for fresh cement foams

Abstract: We prepare and study cement foam samples with well-controlled structure, i.e. containing monodisperse bubbles. We observe that the foam structure often changes before cement setting and identify ripening as the major destabilization mechanism at stake. Drainage plays only a minor role in cement foam destabilization except when bubble size is large. Then we show that a single stability criterion can be defined, for a large range of cement foams with different formulations. This criterion involves the bubble rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Therefore, numerous works are still devoted to elucidate the link between their microstructure and their macroscopic properties, such as thermal, acoustical, mechanical, and transport properties (Despois and Mortensen, 2005;Doutres et al, 2011;Gibson and Ashby, 1997;Jang et al, 2008;Kumar and Topin, 2014). Recently, mineral solid foams, made from cement or geopolymer or gypsum, have been studied for their applications as building materials, requiring a good compromise between mechanical strength, and sound and/or thermal insulation (Chevillotte et al, 2013;Feneuil et al, 2019;Hung et al, 2014;Kaddami and Pitois, 2019;Zhang et al, 2014). This kind of solid foam differs from polymeric foams, which are widely used for sound and/or thermal insulation by both their wide range of porosity (from 0.65 to 0.95) and their highly stiff porous frames.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous works are still devoted to elucidate the link between their microstructure and their macroscopic properties, such as thermal, acoustical, mechanical, and transport properties (Despois and Mortensen, 2005;Doutres et al, 2011;Gibson and Ashby, 1997;Jang et al, 2008;Kumar and Topin, 2014). Recently, mineral solid foams, made from cement or geopolymer or gypsum, have been studied for their applications as building materials, requiring a good compromise between mechanical strength, and sound and/or thermal insulation (Chevillotte et al, 2013;Feneuil et al, 2019;Hung et al, 2014;Kaddami and Pitois, 2019;Zhang et al, 2014). This kind of solid foam differs from polymeric foams, which are widely used for sound and/or thermal insulation by both their wide range of porosity (from 0.65 to 0.95) and their highly stiff porous frames.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that the arrest of coarsening is controled by the ratio between the Laplace pressure γ/R 32 , which drives coarsening, and the resistance of the solid interstitial network, characterized either by its yield stress σ Y [14] or its shear modulus G [53]. The first Laplace term decreases with time, at most by a factor 3 (Fig.…”
Section: B Controlling Pore Size Through Setting Timementioning
confidence: 93%
“…The fresh foam is indeed an unstable fluid structure, which evolves through the combined effects of gravity-induced drainage, ripening due to gas transfer between bubbles, and bubble fusion called coalescence [13]. More precisely, for a given setting time, Feneuil et al have shown that the stability of a cement foam is governed by the ratio between the yield stress of the fresh material, and the Laplace pressure, given by γ/R, with γ the surface tension of the solution, and R the bubble radius [14]. However, we so far do not know how this criterion evolves as the setting time is changed among various materials.…”
Section: Introductionmentioning
confidence: 99%
“…Bey et al worked with monodisperse bubbles to show that, indeed, if the elastic energy of the medium is higher than the surface energy coarsening is halted 9 . Lesov et al and Feneuil et al measured an arrest once the continuous phase yield stress was higher than Laplace pressure 10 , 11 .…”
Section: Introductionmentioning
confidence: 98%